Lessons learned and remaining challenges - Diao, Xinshen; Thurlow, James (International Food Policy Research Institute, 2012)
The 2000s has been Africa’s “decade of growth.” For the first time since the 1970s, Africa has not been the slowest growing developing region in world. This was not necessarily because the rest of the world did badly—economic growth in Africa was faster in the 2000s than in previous decades. This growth acceleration was in spite of the food and financial crises, and subsequent global recession, which Africa appears to have weathered relatively well. Of course, economic growth is not the only measure of development, and the continent’s success in improving social indicators has been less impressive. Poverty and malnutrition remain severe and widespread, and the absolute number of poor people has continued to rise. Agriculture has also lagged behind national economic growth in most countries, thus further entrenching the rural–urban divide. In response to these conditions, many African governments have endorsed the Comprehensive Africa Agriculture Development Programme (CAADP), in which they commit to achieving at least 6 percent annual agricultural growth by allocating at least 10 percent of their national budgets to agricultural investments.